Relaxant Effects of Curcuma aeruginosa Rhizome Extracts on Isolated Rat Gastric Fundus and Ileum Contraction - Thaina, Peerarat; Bumrungwong, Nisita; Wongnawa, Malinee; Subhadhirasakul, Sanan; Yusakul, Gorawit (Trends in Sciences, 2024)
Curcuma aeruginosa (CA) rhizomes are used in traditional medicine as gastrointestinal remedies, postpartum care and uterine issues. However, its effects on gastrointestinal motility have not yet been explored. Extracts of CA rhizomes prepared using chloroform, methanol and water were evaluated for their effects on gastrointestinal contractions using isolated rat gastric fundus and ileum. Varied solvents aim for extraction of different compounds of CA rhizome. In the ileum, the 3 extracts did not significantly affect spontaneous contractions, but significantly reduced contractions induced by acetylcholine (ACh, 0.3 µM) and KCl (40 mM) in a concentration-dependent manner. The order of potency, based on ACh-induced contraction, was chloroform > methanol > water extracts, with respective IC50 values of 0.025 ± 0.001, 0.46 ± 0.02 and 2.57 ± 0.47 mg/mL. Similar potency order against KCl-induced contraction was observed, with IC50 values of 0.011 ± 0.002, 0.47 ± 0.06 and 1.18 ± 0.18 mg/mL, respectively. In the isolated gastric fundus model, both methanol and water extracts resulted in an increase in the force of contraction in the absence of stimulation. However, when ACh (0.3 µM) was introduced, the methanol and water extracts exhibited a concentration-dependent reduction in contractions, with IC50 values of 0.62 ± 0.06 and 2.30 ± 0.32 mg/mL, respectively. As for KCl (40 mM)-induced contraction, only the highest concentration of the water extract (3.75 mg/mL) significantly decreased the contraction by 41.29 ± 2.94 %. CA extract demonstrated relaxant effects on both isolated rat gastric fundus and ileal contractions induced by ACh and KCl. These findings support the use of CA in traditional medicine as a gastrointestinal remedy. These extracts have the potential to be used as antispasmodics and to treat infectious and non-infectious diarrhea, the latter of which occurs in functional gastrointestinal diseases. It might also be useful as a gastroprokinetic. HIGHLIGHTS C. aeruginosa extracts had no impact on rat ileum’s spontaneous contraction Extracts caused dose-dependent relaxation of precontracted ileum Extracts enhanced spontaneous contraction of isolated gastric fundus Extracts induced relaxation in the precontracted isolated gastric fundus GRAPHICAL ABSTRACT